APA Handbook of Sexuality and Psychology, Vol. 2: Contextual Approaches. 2014
DOI: 10.1037/14194-006
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and culture.

Abstract: Culture is a system in which our products produce us, we are made by what we make, and human objectifications objectify consciousness in particular ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 255 publications
0
11
0
2
Order By: Relevance
“…All of these are compelling reasons to have diverse samples in sex research. Despite these reasons, the scientific study of sex emerged in the West and has remained largely Western-European (Agocha et al, 2014). Based on this historical tradition, we hypothesized that most contemporary sex research in scientific sexuality journals would rely on WEIRD and predominantly male samples.…”
Section: National Context: the Weirdness Of Sex Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these are compelling reasons to have diverse samples in sex research. Despite these reasons, the scientific study of sex emerged in the West and has remained largely Western-European (Agocha et al, 2014). Based on this historical tradition, we hypothesized that most contemporary sex research in scientific sexuality journals would rely on WEIRD and predominantly male samples.…”
Section: National Context: the Weirdness Of Sex Researchmentioning
confidence: 99%
“…Historically, the scientific study of sexuality has been a Western-European enterprise (Agocha et al, 2014). An early analysis of articles published between 1971-1995 in the Archives of Sexual Behavior and the Journal of Sex Research demonstrated that sex research was limited by a lack of ethnic diversity in study populations (Wiederman et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Culture is no doubt an important framework for the understanding of sexuality (Agocha, Asencio & Decena, 2014) and while there are various studies that have looked at differences in permissiveness and acceptance of sexuality between countries and regions (e.g., Baumeister & Mendoza, 2011;Haavio-Mannila & Kontula, 2003), they are susceptible to change in currently highly globalised societies. In this respect, despite expecting to find substantial differences between older people form the North, centre, and South of Europe, a recent study by Fischer et al (2018) did not find origin to be a predictor variable of sexual activity in malefemale couples aged between 60 and 75 in Norway, Denmark, Belgium and Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…This is however an important area for consideration as cultural meanings and input are imbued into all elements of sexuality providing a significant framework for constructions of SRH and vice versa [21]. As Agocha, Asencio and Decena [22] explain, “the values, beliefs, and behaviours associated with sexuality reveals a great deal about the larger beliefs and values of the society they inhabit or from which they originate”. Considering 1.5 generation migrants’ cross-cultural positionality taking time to consider and manage the expectations of two cultures may result in delayed help-seeking leading to SRH issues becoming more serious (e.g., sexually transmitted infections (STIs) being transmitted to others or unmanaged pregnancy) [11, 21].…”
Section: Introductionmentioning
confidence: 99%